2006
DOI: 10.1099/vir.0.81499-0
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the C-terminal domain of soybean mosaic virus coat protein for subunit interactions

Abstract: The potyvirus coat protein (CP) is involved in aphid transmission, cell-to-cell movement and virus assembly, not only by binding to viral RNA, but also by self-interaction or interactions with other factors. In this study, a number of CP mutants of Soybean mosaic virus (SMV) containing deletions and site-directed mutations were generated and cloned into yeast two-hybrid vectors. Interaction was confirmed by the expression of reporter genes, including HIS3, ADE2 and MEL1, in yeast strain AH109. Deletion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
0
18
1
1
Order By: Relevance
“…Most experiments were carried out using the G7 strain, but fiber diffraction experiments used both strains, and because of the better orientation and higher quality of the diffraction data, data from the G6 strain were used in the analysis. The coat proteins of the two strains differ at only 3 amino acid residues (33), and the substitutions are all conservative and within 20 residues of the N terminus, known to be located at the outer surface of the virion and probably disordered (5,56). PVX was purified and stored as previously described (52).…”
Section: Methodsmentioning
confidence: 99%
“…Most experiments were carried out using the G7 strain, but fiber diffraction experiments used both strains, and because of the better orientation and higher quality of the diffraction data, data from the G6 strain were used in the analysis. The coat proteins of the two strains differ at only 3 amino acid residues (33), and the substitutions are all conservative and within 20 residues of the N terminus, known to be located at the outer surface of the virion and probably disordered (5,56). PVX was purified and stored as previously described (52).…”
Section: Methodsmentioning
confidence: 99%
“…The KLSC and PTK motifs in HC‐Pro, and the DAG motif in CP, have been confirmed to be involved in SMV aphid transmission (Jossey et al ., ; Seo et al ., ). Additional amino acid sequences near the carboxyl terminus of HC‐Pro and the putatively exposed carboxyl terminus of CP have been implicated in aphid transmissibility of SMV (Jossey et al ., ; Kang et al ., ; Seo et al ., ).…”
Section: Transmissionmentioning
confidence: 99%
“…For instance, using expression in E. coli, Jagadish et al (1993) showed that Arg 194 and Asp 238 of JGMV are required for the assembly process but were not necessarily involved in forming the predicted salt bridge. The C-terminal domain of SMV CP is required for CP-CP self-interaction (Kang et al, 2006). The C-terminal domain of SMV CP is required for CP-CP self-interaction (Kang et al, 2006).…”
Section: B Other Rod-shaped Virusesmentioning
confidence: 99%